Overexpression of bovine leukemia virus receptor SLC7A1/CAT1 enhances cellular susceptibility to BLV infection on luminescence syncytium induction assay (LuSIA) - Hirotaka Sato; Lanlan Bai; Liushiqi Borjigin; Yoko Aida (Virology Journal, 2020)
Abstract Bovine leukemia virus (BLV) causes enzootic bovine leukosis, the most common neoplastic disease in cattle. We previously reported the development and protocol of the luminescence syncytium induction assay (LuSIA), a method for evaluating BLV infectivity based on CC81-GREMG cells. These cells form syncytia expressing enhanced green fluorescent protein when co-cultured with BLV-infected cells. Recently, we confirmed CAT1/SLC7A1 functions as a receptor of BLV. Here, we focused on CAT1/SLC7A1 to increase the sensitivity of LuSIA. We constructed a bovine CAT1-expressing plasmid and established a new CC81-GREMG-derived reporter cell line highly expressing bovine CAT1 (CC81-GREMG-CAT1). The new LuSIA protocol using CC81-GREMG-CAT1 cells measures cell-to-cell infectivity and cell-free infectivity of BLV faster and with greater sensitivity than the previous protocol using CC81-GREMG. The new LuSIA protocol is quantitative and more sensitive than the previous assay based on CC81-GREMG cells and will facilitate the development of several new BLV assays.